Evaluation of interventions led by pharmacists in antimicrobial stewardship programs in low- and middle-income countries: a systematic literature review - Tatiana Aporta Marins; Graciele Riveres de Jesus; Marisa Holubar; Jorge L. Salinas; Gabrielli Pare Guglielmi; Vivian Lin; Silvana Maria de Almeida (Cambridge University Press, 2024)
Abstract Objective: We performed a systematic literature review to identify and describe pharmacist-led antimicrobial stewardship programs (ASPs) interventions in low- and middle-income countries (LMICs). Design: Systematic literature review. Methods: We searched PubMed for studies evaluating pharmacist-led ASP interventions in LMICs from January 1, 2012, to November 4, 2023. We evaluated the article's country of origin, described ASP interventions, and analyzed their reported outcomes. Results: Twenty-four studies were included; ten were conducted in China, two in India, two in Thailand, five in Africa, three in Latin America, and two in the Middle East. The predominant interventions in the studies were education and training followed by audit and feedback. The outcomes reported included reduction in antimicrobial consumption, cost reduction, shortening of the duration of antimicrobial therapy, and de-escalation. Conclusions: Our findings reinforce the importance of clinical pharmacists leading interventions related to antimicrobial stewardship in LMCIs and the global importance of investing in Infectious Disease training.